A Mixed-refrigerant Miniature Joule-Thomson Cooler Driven by a Linear Compressor - Cao Haishan; Meng Qinghang; Tong Xin; Liu Biqiang; Wang Xiaotao (Zhileng xuebao)
Many electronic devices can benefit from operating at low temperatures. However, the widespread use of cryogenic electronic devices is limited by the miniaturization of cryocoolers. In this study, a closed Joule-Thomson (JT) cooling system based on a multicomponent mixture was investigated. The system comprised a Hampson-JT microcooler and a linear compressor. The working fluid was a ternary mixture with a molar concentration of 39% methane, 20% ethane, and 41% isobutane. The cooling performance of a refrigerator under different conditions was studied experimentally. The results show that the microcooler can achieve a cold-end temperature of 165 K under 0.10–1.77 MPa and 0.14–1.90 MPa pressure, and 198 K under 0.36–1.73 MPa and 0.18–1.36 MPa pressure. The compact structure of the cooling system promotes the application of cryogenic electronic devices in the fields of military, space science, and biomedicine.